Natural tolerance/resistance of citrus plants to Citrus tristeza disease - D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Since tristeza is the most serious citrus virus disease worldwide, knowing the natural defense systems of citrus plants is still considered the main control approach. In this paper an account is given of the attempts to use CTV tolerant/resistant cultivars and rootstocks and classical cross-protection programmes to contain tristeza disease.